Pengaruh Struktur Modal dan Likuiditas Terhadap Profitabilitas Bank Konvensional yang Terdaftar pada Bursa Efek Indonesia - Ju Shandra; Mahroji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate the relationship between capital structure and liquidity with profitability of conventional banks in Indonesia. This analysis uses secondary data from 24 banks listed on the Indonesia Stock Exchange between 2021 and 2023. The analytical approach used includes multiple linear regression with classical assumption tests and hypothesis testing. The findings show that while capital structure has a significant positive impact on profitability, liquidity has no impact on profitability. The limitation of this study lies in the differences in the results of financial ratio analysis which may be influenced by variations in calculation methods. This study suggests that banking companies should pay attention to capital structure management to improve profitability. The contribution of this study lies in providing insights that can be used by bank managers and researchers in making strategic decisions related to capital structure and liquidity. Further research is expected to consider more comprehensive data as well as more standardized methods to improve the accuracy of the research results.